Rancang Bangun Sistem Informasi Surat Keterangan Kematian Pasien Rawat Inap Menggunakan Metode Extreme Programming - Sulastri, Imas Yeti; Syahidin, Yuda; Gunawan, Erix; Sukmawijaya, Jeri (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Evolved technology can support the performance of hospital employees, one of which is in the inpatient medical record installation, namely, making inpatient death certificates that have not been computerized. Several problems were found at the medical record installation, namely delays in making patient death certificates and incomplete filling of patient death certificates by doctors, which reduced the quality of reporting and was inaccurate. Therefore, an information system is needed to streamline doctors' performance in making death certificates for inpatients in a thorough, fast, and accurate manner. Data collection methods include literature study, interviews, and observation with descriptive analysis. The system development method uses the extreme programming method. The results of the information system design using the selected methods can streamline doctors' performance in making death certificates for inpatients so that reporting carried out by medical record officers produces accurate data. In addition, this information system can maximize patient services and increase the quality of services at the hospital.